2020
DOI: 10.3390/mi11060542
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Analysis of Nanofluidic Ion Current Rectification Using a Metal-Dielectric Janus Nanopore Driven by Induced-Charge Electrokinetic Phenomena

Abstract: We propose herein a unique mechanism of generating tunable surface charges in a metal-dielectric Janus nanopore for the development of nanofluidic ion diode, wherein an uncharged metallic nanochannel is in serial connection with a dielectric nanopore of fixed surface charge. In response to an external electric field supplied by two probes located on both sides of the asymmetric Janus nanopore, the metallic portion of the nanochannel is electrochemically polarized, so that a critical junction is formed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…The finite element simulation technology has been conducted by many researchers to explore the theoretical issues of nanochannels. ,, In our previous studies, , we have demonstrated that the enrichment and depletion of the ion concentration in the asymmetrical nanochannel can cause ion current rectification (ICR). Other researchers have similar results.…”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The finite element simulation technology has been conducted by many researchers to explore the theoretical issues of nanochannels. ,, In our previous studies, , we have demonstrated that the enrichment and depletion of the ion concentration in the asymmetrical nanochannel can cause ion current rectification (ICR). Other researchers have similar results.…”
Section: Simulationmentioning
confidence: 99%
“…In this case, single graphene nanopore models are constructed by finite element simulation (FEM) technology. Finite element simulation (FEM) is a popular simulation method for studying nanopores and related applications. In addition, compared with FEM, the NOM is an excellent computational approach that can be used for modeling. The solution of partial differential equations (PDEs) plays a crucial role in various fields of science and engineering.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the diode-like ion current rectification (ICR) behavior, which assures ions preferentially transporting in one direction and hence amplifies ionic current, can be observed when the symmetry of ionic concentration profiles along the axis of a nanopore is broken [ 18 , 19 ]. Considerable experimental [ 20 , 21 , 22 ] and theoretical [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] efforts have been made on ICR in nanofluidics and all these studies concluded that the ICR property only can emerge in case the pore size is comparable to the EDL thickness.…”
Section: Introductionmentioning
confidence: 99%